Female and male serum reference intervals for challenging sex and precursor steroids by liquid chromatography - tandem mass spectrometry. Issue 197 (March 2020) - Mezzullo, Marco; Pelusi, Carla; Fazzini, Alessia; Repaci, Andrea; Di Dalmazi, Guido; Gambineri, Alessandra; Pagotto, Uberto; Fanelli, Flaminia
Highlights: Four challenging steroids are measured in serum by a novel validated LC-MS/MS assay. The ECLIA for estradiol measurement was in good agreement with the LC-MS/MS method. The RIA for estrone measurement was in severe disagreement with the LC-MS/MS method. Estrogens and dihydrotestosterone varied with menopause in women but not with age in men. 17-Hydroxypregnenolone levels depended on sex, menopause in women and age in men. Abstract: Measuring some sex and precursor steroids is still challenging even by liquid chromatography – tandem mass spectrometry (LC-MS/MS), and few normal values are available. We developed a LC-MS/MS method for estradiol, estrone, dihydrotestosterone and 17-hydroxypregnenolone measurement, compared it with direct immunoassays, and generated sex, age, menopausal and menstrual status specific reference intervals. Liquid-liquid extraction was optimized on 300 μL serum spiked with isotopic internal standards. A 2D-LC system allowed on-line purification and separation in 11 min run. Electrospray ionization was enhanced by ammonium fluoride. MS-detection was obtained by multiple reaction monitoring. Direct ECLIA for estradiol (n = 80) and RIA for estrone (n = 41) were compared with LC-MS/MS. Reference values were estimated in healthy, lean women in reproductive age (n = 118), menopausal women (n = 33) and men (n = 159). The assay showed satisfying imprecision, trueness, recovery and selectivity. Adequate functional sensitivity was achieved for measuring estrone (18.1 pmol/L) and 17-hydroxypregnenolone (117 pmol/L) in all subjects, and estradiol (35.9 pmol/L) and dihydrotestosterone (134 pmol/L) in women in reproductive age and men, but not in menopausal women. Compared with LC-MS/MS, immunoassays showed good agreement for estradiol but severe disagreement for estrone. Estrogens exhibited sex, menopausal and menstrual variations. Dihydrotestosterone and 17-hydroxypregnenolone depended on sex and menopause, the latter also declining with age in men. Strictly defined reference intervals in the adult female and male population were generated for challenging steroids such as estrogens, dihydrotestosterone and 17-hydroxypregnenolone by a novel LC-MS/MS method. Our achievement can be used to deepen the comprehension of several endocrine diseases.